Beckman Model KF-4 Aquameter Titrator - Armstrong & Hess
The KF-4 Aquameter was included in the new product show at the Pittsburgh Conference in March 1970.
Keywords: Scientific apparatus and instruments; Volumetric analysis; Beckman Instruments, Inc.